4Cos²x - Sin2x - 4Sin²x = 1
4Cos²x - 2SinxCosx - 4Sin²x - Sin²x - Cos²x = 0
5Sin²x + 2SinxCosx - 3Cos²x = 0
Разделим почленно на Cos²x ≠ 0 , получим :
5tg²x + 2tgx - 3 = 0
Сделаем замену :
tgx = m
5m² + 2m - 3 = 0
D = 2² - 4 * 5 * (- 3) = 4 + 60 = 64 = 8²
![m_{1}=\frac{-2+8}{10}=0,6\\\\m_{2}=\frac{-2-8}{10}=-1\\\\tgx=0,6\\\\x=arctg0,6+\pi n,n\in Z\\\\tgx=-1\\\\x=-\frac{\pi }{4}+\pi n,n\in Z m_{1}=\frac{-2+8}{10}=0,6\\\\m_{2}=\frac{-2-8}{10}=-1\\\\tgx=0,6\\\\x=arctg0,6+\pi n,n\in Z\\\\tgx=-1\\\\x=-\frac{\pi }{4}+\pi n,n\in Z](https://tex.z-dn.net/?f=m_%7B1%7D%3D%5Cfrac%7B-2%2B8%7D%7B10%7D%3D0%2C6%5C%5C%5C%5Cm_%7B2%7D%3D%5Cfrac%7B-2-8%7D%7B10%7D%3D-1%5C%5C%5C%5Ctgx%3D0%2C6%5C%5C%5C%5Cx%3Darctg0%2C6%2B%5Cpi%20n%2Cn%5Cin%20Z%5C%5C%5C%5Ctgx%3D-1%5C%5C%5C%5Cx%3D-%5Cfrac%7B%5Cpi%20%7D%7B4%7D%2B%5Cpi%20n%2Cn%5Cin%20Z)